Common Pathogenic Effects of Missense Mutations in the P-Type ATPase ATP13A2 (PARK9) Associated with Early-Onset Parkinsonism - Podhajska, Agata; Musso, Alessandra; Trancikova, Alzbeta; Stafa, Klodjan; Moser, Roger; Sonnay, Sarah; Glauser, Liliane; Moore, Darren J. (PloS one, 2012)
Mutations in the ATP13A2 gene (PARK9) cause autosomal recessive, juvenile-onset Kufor-Rakeb syndrome (KRS), a neurodegenerative disease characterized by parkinsonism. KRS mutations produce truncated forms of ATP13A2 with impaired protein stability resulting in a loss-of-function. Recently, homozygous and heterozygous missense mutations in ATP13A2 have been identified in subjects with early-onset parkinsonism. The mechanism(s) by which missense mutations potentially cause parkinsonism are not understood at present. Here, we demonstrate that homozygous F182L, G504R and G877R missense mutations commonly impair the protein stability of ATP13A2 leading to its enhanced degradation by the proteasome. ATP13A2 normally localizes to endosomal and lysosomal membranes in neurons and the F182L and G504R mutations disrupt this vesicular localization and promote the mislocalization of ATP13A2 to the endoplasmic reticulum. Heterozygous T12M, G533R and A746T mutations do not obviously alter protein stability or subcellular localization but instead impair the ATPase activity of microsomal ATP13A2 whereas homozygous missense mutations disrupt the microsomal localization of ATP13A2. The overexpression of ATP13A2 missense mutants in SH-SY5Y neural cells does not compromise cellular viability suggesting that these mutant proteins lack intrinsic toxicity. However, the overexpression of wild-type ATP13A2 may impair neuronal integrity as it causes a trend of reduced neurite outgrowth of primary cortical neurons, whereas the majority of disease-associated missense mutations lack this ability. Finally, ATP13A2 overexpression sensitizes cortical neurons to neurite shortening induced by exposure to cadmium or nickel ions, supporting a functional interaction between ATP13A2 and heavy metals in post-mitotic neurons, whereas missense mutations influence this sensitizing effect. Collectively, our study provides support for common loss-of-function effects of homozygous and heterozygous missense mutations in ATP13A2 associated with early-onset forms of parkinsonism.